Pretty things : [compact disc, unabridged] / a novel - Brown, Janelle (Random House Audio, an imprint of the Penguin Random House Audio Publishing Group, 2020)
"Nina once bought into the idea that her fancy liberal arts degree would lead to a fulfilling career. When that dream crashed, she turned to stealing from rich kids in L.A. alongside her wily Irish boyfriend, Lachlan. Nina learned from the best: Her mother was the original con artist, hustling to give her daughter a decent childhood despite their wayward life. But when her mom gets sick, Nina puts everything on the line to help her, even if it means running her most audacious, dangerous scam yet. Vanessa is a privileged young heiress who wanted to make her mark in the world. Instead she becomes an Instagram influencer--traveling the globe, receiving free clothes and products, and posing for pictures in exotic locales. But behind the covetable façade is a life marked by tragedy. After a broken engagement, Vanessa retreats to her family's sprawling mountain estate, Stonehaven: A mansion of dark secrets not just from Vanessa's past, but from that of a lost and troubled girl named Nina. Nina, Vanessa, and Lachlan's paths collide here, on the cold shores of Lake Tahoe, where their intertwined lives give way to a winter of aspiration and desire, duplicity and revenge. This dazzling, twisty, mesmerizing novel showcases acclaimed author Janelle Brown at her best, as two brilliant, damaged women try to survive the greatest game of deceit and destruction they will ever play"--